Improving Student Character through Role Playing Senja Script Scene 2: Ki Hadjar Dewantara's Perspective - Danubrata, Gunawan Wibisana; Uus Karwati; Reni Haerani (Journal of Practice Learning and Educational Development, 2026)
The teaching of arts and culture in schools, including theater, plays a crucial role in shaping students' appreciation, imagination, and creativity towards aesthetic values and local and global culture. Through role-playing, performances, and appreciation activities, students not only learn performance techniques but also understand complex human experiences such as conflict, sacrifice, and hope. The success of this process is largely determined by the teacher's choice of teaching methods, especially in the context of traditional Indonesian theater for 10th grade high school students, which requires a balance between artistic aspects and character building. The role- playing method has proven to be effective because it encourages students to explore feelings, attitudes, values, skills, and knowledge through performance and reflective discussion after the performance. This study examines the application of role playing in the script Senja Adegan 2 by Gunawan Wibisana Danubrata, highlighting its relevance to Ki Hadjar Dewantara's perspective, which emphasizes the harmony of thought, feeling, and intention as the basis of character. Through analysis of the performance process and results, the findings are expected to contribute to the development of creative, contextual, student-centered theater learning strategies that are in line with national educational values and character education objectives in secondary schools.